CaRPE: the Carbon Reduction Potential Evaluation tool for building climate mitigation scenarios on US agricultural lands. (14th December 2022) - Manter, Daniel K; Moore, Jennifer M
Abstract: The Carbon Reduction Potential Evaluation (CaRPE) tool is a web-based interactive tool that integrates two databases for the USA collected at county/multi-county scales to visualize and estimate the climate benefits of implementing a variety of conservation practices on croplands and grazing lands. The COMET-Planner tool provides county/multi-county carbon sequestration and greenhouse gas emission reduction coefficients associated with the adoption of climate-smart agricultural management practices. The CaRPE tool couples these coefficients, reported in tonnes of carbon dioxide equivalents (CO2 e) per acre per year, with county-level cropland and grazing land acres extracted from the US Agricultural Census. The CaRPE graphical user interface allows users to quickly and easily build and export scenarios of new conservation practice adoption on desired acreages and locations at state, regional or national scales. Results are in tonnes CO2 e per year, and each scenario can be exported in tabular and map formats at the selected scales. Existing county-level cropland acreage data provide the upper boundaries for acres of adoption and can be modified based on specific goals established by the user.The output may be used to develop potential targets of adoption and help inform decisions related to resource prioritization and planning efforts. In collaboration with local experts and farmer-led organizations, the results can provide a key starting block to prioritize practices and areas that contribute to climate benefits. As the underlying databases and models are updated and improved, CaRPE can be revised accordingly to increase accuracy and enhance applicability. The CaRPE tool and the user guide are available at: Database URL : https://carpe.shinyapps.io/CarpeTool/